The Mediating Role of Job Satisfaction in the Influence of Training and Career Development on Employee Performance: A Study at PT Jasa Raharja, Bali - ISMAYA, I Gusti Ayu Paramita; SARA, I Made; INDIANI, Ni Luh Putu (PT Keberlanjutan Strategis Indonesia, 2025)
The insurance industry plays a crucial role in supporting national economic development by providing risk protection to the community. PT Jasa Raharja, as one of the State-Owned Enterprises (BUMN) engaged in traffic accident insurance, has a strategic role in providing social security to the community, especially victims of traffic accidents in Indonesia. Therefore, improving employee performance is the main focus of the organization in carrying out its duties and responsibilities optimally in order to provide the best service for the public. This study aims to analyze the implementation of training, career development, job satisfaction, and employee performance at PT Jasa Raharja Bali. Data were collected through a survey of 51 employees who were sampled in the study. The results of data collection were processed using Partial Least Squares Structural Equation Modeling. The results showed that training has a significant positive effect on employee performance and also on job satisfaction. Career development has no significant effect on employee performance, but a significant positive impact on job satisfaction. Job satisfaction has a significant positive effect on performance. In addition, it was found that job satisfaction is unable to mediate the effect of training on employee performance, but is able to mediate the effect of career development on employee performance partially.